Kajian Dampak Promosi Terhadap Tingkat Penjualan Produk Selular PT. Bakrie Telecom Esia-Manado - Prestasi, Hadi; Mantjoro, Eddy (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: The objectives of the research are to determine the impact on the level of sales promotions. Methodology used in this research is qualitative descriptive which described it in detail starting from the general conditions to the promotion and implementation of how the volume of sales at PT. Bakrie Telecom Esia-Manado. The number of sample was 30 respondentscoposed of the Sale and respondents (Owner Counter), civil servants, private employees, students, housewives. To get data we used a structured interview instrument that is directed at informants. Analysis of data from data collection, data classification, data display, to the inference. To prove the results of the study is strengthened by data on the interview, sales volume, and promotions conducted by PT. Bakrie Telecom Esia-Manado. The results showed that the Â mobile card products PT. Bakrie Telecom Esia-Manado is quite good, especially at the rate or rates of use cellular card. When compared with the rate of its peers are much cheaper there even in the development of new program bundling with other vendor phone Â Blackberry, Samsung, HTC, Alcatel, Iphone. Promotion is done is not maximized, it is indicated there are still many people not familiar with the products produced by the company. an effect on the level of sales promotion cellular cards PT. Bakrie Telecom Esia-Manado. Visible indication that the increase in sales in each quartile for the three years 2010 to the third quartile of 2011sebesar 1%, this happens because of promotion and advertising firm is not maximized. From the research it can be concluded that sales promotion of PT. Bakrie Telecom Esia-Manado indicated there is an impact. For that the company should be able to make the scale of priorities is the promotion and advertising so that people know the products marketed by the company. Primarily engaged in the promotion of the price offered, because it is owned by the company's advantage. Key word: promotion, product sales